Perbelanjaan Perkahwinan Dalam Masyarakat Melayu Muslim: Analisis Literatur - Syh Noorul Madihah, Syed Husin; Raihanah, Azahari; Asmak, Ab. Rahman (2016)
Marriage expenses is a necessity within the process of a marriage. In the Muslim community, the couple will start spending for a wedding preparations prior the couple consolidated. Couples who plan to marry must provide a certain amount of money to ensure that their desire to marry reached. There are various studies have done which linked towards marriage expenses for the Muslim community. This article will review about marriage expenses for the Muslim community of various forms of writing such as academic books, dissertations, theses and journal articles. This study found that there are four themes which has to do with the topic discussed. Generally, studies in that themes only discussed issues related to the marriage expenses indirectly without provide any review on how Muslim communities manage it. As a result from the data analysis, this paper found that there is a need to conduct a special studies on this topic to fill in the gap in regards of Islamic family studies. This is to provide a comprehensive review and analysis of the Muslim community expenses from the perspective of marriage legislation.